Integration Of Science, Knowledge, And Religion In Learning Calistung: A Case Study At Berkah Amanah Private Tutoring Calistung - Rumiati, Rumiati; Wardhana, Kautsar Eka; Kholifah, Yusnia Binti (Doctoral Program of Social Science Pasundan University, 2025)
This research investigates the practice of integrating knowledge, science, and religion in early childhood education, specifically at the 'Berkah Amanah' Private Calistung Tutoring Center. In light of the prevailing tendency to separate science and religious education, this study seeks to explore how these two domains are harmoniously integrated in the teaching of reading, writing, and arithmetic (calistung). Employing a qualitative case study approach, this research employs observation, interviews, and document analysis to uncover two primary practices that facilitate this integration. Firstly, a visual-thematic learning method is employed, which combines cognitive science principles with religious content. Second, the cultivation of learning etiquette (adab) serves as a foundational element for cognitive readiness. Through an analysis using Ian G. Barbour's typology, it is evident that the practices at this institution align with the Dialogue and Integration models. This suggests that the unification of science and religion can be effectively implemented within the context of primary education. This study explores the practice of integrating science, knowledge, and religion in early childhood education, by taking a case study at Berkah Amanah Private Tutoring Center. Amidst the tendency of dichotomy between science and religion education, this study aims to identify how the two domains are synthesized in learning to read, write, and count (calistung). This study uses a qualitative case study approach, involving observation, interviews, and document analysis. The results show that integration is realized through two main practices: (1) a visual-thematic learning method that combines cognitive science principles with religious content, and (2) instilling learning etiquette as a foundation for cognitive readiness. Analysis using Ian G. Barbour's typology shows that the practice at this institution represents the Dialogue and Integration model, proving that the integration of science and religion can be implemented effectively in the context of elementary education.